The Cultural Relationship between Christianity and Technology for the Practice of Christian Mission - Min Hyoung Lee (Asosiasi Khazanah Cendekia, 2024)
The involvement of all members of society in the advancement of technology is becoming a crucial aspect since the pace of technological advancement has accelerated markedly. Christianity, as a constituent of society, is also being called upon to reflect on technology and to apply it in tangible ways within the social context. This study examines how Christianity can contribute to the formation of social norms reflected in the development and operation of technology. The methods that this study uses include an initial investigation undertaken into the concept of technology based on the theory of the philosopher of technology, Langdon Winner. Subsequently, the study elucidates the interrelationship between Christianity and technology by demonstrating that technology and Christianity are human cultural systems on an equal footing. Finally, this study endeavors to facilitate an interdisciplinary dialogue between the philosophy of technology and public theology to postulate the potential for technology and Christianity to exert reciprocal influence on one another. Throughout these methods, this research defines the cultural relationship between technology and Christianity and finds influencing the trajectory of technological advancement from a Christian perspective constitutes a missional practice.